2009
DOI: 10.3989/scimar.2009.73s1047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on specific gravity and viability of eggs of a North American minnow (Cyprinidae)

Abstract: SUMMARY: The influence of salinity on survival, specific gravity, and size of eggs of the endangered Hybognathus amarus (Rio Grande silvery minnow) was studied to provide insight into factors affecting their potential dispersal and fate. Under low salinity conditions egg specific gravity declined significantly in the first hour after spawning as the perivitelline space of the egg filled with water. Egg specific gravity achieved a minimum value approximately 1 h post-spawning and remained approximately constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“… References: 1 Cowley et al. (); 2 Welker and Scarnecchia (); 3 Matthews and Maness (); 4 Ostrand and Wilde (); 5 Echelle, Echelle and Hill (); 6 Bryan et al. (); 7 Lutterschmidt and Hutchison (); 8 Bonner et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… References: 1 Cowley et al. (); 2 Welker and Scarnecchia (); 3 Matthews and Maness (); 4 Ostrand and Wilde (); 5 Echelle, Echelle and Hill (); 6 Bryan et al. (); 7 Lutterschmidt and Hutchison (); 8 Bonner et al.…”
Section: Resultsmentioning
confidence: 99%
“…Mortality of the three species was 100% at salinities greater than 22‰ (Ostrand & Wilde, ). Increased salinity can cause elevated mortality of Rio Grande silvery minnow eggs by reducing the diameter and increasing the specific gravity of the eggs, thereby changing transport dynamics (Cowley, Alleman, Sallenave, McShane & Shirey, ). Further, Rio Grande silvery minnow eggs remain in suspension longer at higher turbidities than at lower turbidities (Medley & Shirey, ).…”
Section: Resultsmentioning
confidence: 99%
“…The second less common pattern was passive dispersal with retention of propagules in the upriver reach where residents remained at or above Highway 70 throughout their lives (18% of the fish captured at or above Highway 70). Cowley et al (2009) suggested that bidirectional dispersal (downriver displacement and upriver movement) was important in the life history of a similar Great Plains river fish (Rio Grande silvery minnow, Hybognathus amarus). The combined return of young-of-year from downriver and retention as residents suggests that the current success of the population relies on eventually securing a large portion of the population through egg retention in the upriver reach.…”
Section: Discussionmentioning
confidence: 98%
“…The eggs are nonadhesive and semibuoyant, and as long as water velocity is sufficient, the propagules will remain suspended within the water column and drift downriver while development occurs (Platania and Altenbach 1998;Cowley et al 2009). Retention of eggs and fry in slack-water nursery habitat reduces the chances of continued downriver displacement and may be key to successful recruitment into the population (Dudley and Platania 2007;Hoagstrom and Turner 2015).…”
Section: Introductionmentioning
confidence: 98%
“…blastula cells) was demonstrated in Atlantic herring ( Clupea harengus ) (Holliday & Jones 1965) and plaice ( Pleuronectes platessa ) (Holliday & Jones 1967). Moreover, eggs of the freshwater North American minnow ( Hybognathus amarus , Cyprinidae) adapted their specific gravity and volume to the surrounding salinity, revealing an osmotic flux of water out from the periviteline space into the incubation medium (Cowley et al. 2009).…”
Section: Discussionmentioning
confidence: 99%